THE INFLUENCE OF THE PERFORMANCE OF VILLAGE APPARATUS ON IMPROVING THE QUALITY OF PUBLIC SERVICES IN WONOHARJO VILLAGE, PANGANDARAN DISTRICT, PANGANDARAN DISTRICT - Rafiqa Yusrini; Endah Vestikowati; Regi Refian Garis (Yayasan Panca Bakti Wiyata Pangandaran, 2023)
This research is motivated by the lack of optimal improvement in the service process which is thought to be due to the performance of the Wonoharjo Village Officials, Pangandaran District, Pangandaran Regency which is still not optimal, such as the low level of discipline of village officials, the village officials not being optimal in carrying out work quickly, precisely and deftly and the low level of knowledge possessed by village officials. in carrying out services, lack communication skills and are less open to suggestions and criticism of their work. The formulation of the problem is 1) How is the performance of village officials in Wonoharjo Village, Pangandaran District, Pangandaran Regency?, 2) What is the quality of public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency? and 3) How much big influence performance village officials to quality services in Wonoharjo Village, Pangandaran District, Pangandaran Regency?. The research method used in this research is a descriptive analysis method with a quantitative approach. The number of samples in this study was 100 people. In this research, researchers used quantitative data analysis techniques such as determining ranges, determining assessment categories, percentages, coefficient analysis, determination correlation and t test. The research results show that: 1) Performance of Village Officials in Wonoharjo Village, Pangandaran District, Pangandaran Regency has been implemented quite well, 2) The quality of public services in villages in Wonoharjo Village, Pangandaran District, Pangandaran Regency has been implemented quite well, 3) There is an influence of the performance of village officials on improving the quality of public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency by 34.59% . From the results of the hypothesis test, it was obtained that the t count was 7.1999 > from the t table of 1.66055 so that the hypothesis that the author put forward was that there was an influence on the performance of village officials on improving the quality of public services at the Wonoharjo Village office, Pangandaran District, Pangandaran Regency, which could be accepted and had its validity tested.